California polyphony : ethnic voices, musical crossroads - Yang, Mina (Music in American life., 2008)
What does it mean to be "Californian"? Mina Yang suggests an answer that lies at the intersection of musicology, cultural history, and politics. Consisting of a series of musical case studies of major ethnic groups in California, this book approaches the notion of Californian identity from diverse perspectives, each nuanced by class, gender, and sexuality. This most populous and most affluent state in the Union has been setting musical and cultural trends for decades, and Yang's study thoughtfully illuminates the multiculutral nature of its musics.